Construction of Robotic Virtual Laboratory System Based on Unity3D. Issue 7 (March 2020) - Lin, Mu; San, Lijun; Ding, Yu
Abstract: Paper introduces the virtual reality laboratory system based on virtual reality technology. Using the Unity3D engine, the robotic arm is used as the research object to develop the virtual simulation teaching system. The system is released on the PC side and applied to the teaching and training of the mechanical arm structure. Establish a virtual laboratory to realize the first person perspective roaming, on-the-spot observation robot arm structure, assembly virtual interaction simulation, intelligent automatic assembly simulation, solve complex mechanical structure cognitive teaching and assembly planning problems. The application of powerful virtual reality technology to engineering technology teaching has improved the teaching effect and teaching efficiency of mechanical structure cognition, structural assembly training, curriculum design and other teaching links.